Mathematical analysis of bead parameters in MIG welding of stainless steel 304 - Tripathy, Mayank; Khanna, Pradeep (Journal of Production Engineering, 2020)
MIG welding process has gained prominence over the past few decades owing to its versatility, portability, all-position weldability, and ease of automation. These attributes of MIG welding make it suitable for usage in the fabrication and automotive sectors over other conventional welding processes. The present work aims to study the effects of varying the controllable input parameters on the weld bead shape obtained by MIG welding on Stainless Steel-304. The statistical technique of Design of Experiments has been used for a systematic and structured way of experimentation. The linear two-factor interactive and quadratic effects of welding parameters and the response on the parameters were predicted by developing mathematical models using the center composite rotatable design technique. ANOVA analysis was carried out to check the adequacy of the developed models, and response surface methodology was used to analyze the effects of input variables on the outputs through graphical means.